Rejuvenation of Helicobacter pylori–Associated Atrophic Gastritis Through Concerted Actions of Placenta-Derived Mesenchymal Stem Cells Prevented Gastric Cancer - Park, Jong Min; Han, Young Min; Hahm, Ki Baik (Frontiers in Pharmacology, 2021)
Chronic Helicobacter pylori infection caused gastric cancer via progression of precancerous chronic atrophic gastritis (CAG). Therefore, reverting gastric atrophy can be anticipating strategy to prevent H. pylori-associated gastric carcinogenesis. Though eradication can be an answer to break this liaison, in this study, we hypothesized the rejuvenating and restorative actions of mesenchymal stem cells can rejuvenate atrophic gastritis to non-atrophy. Using human placenta derived-mesenchymal stem cells (PD-MSCs) among stem cells, we documented the effects of PD-MSCs or their conditioned medium (CM) on H. pylori-associated CAG in mice/cell model with exploration of their molecular mechanisms. We compared the changes of fecal microbiomes after PD-MSCs. After 10 times administration of PD-MSCs during chronic H. pylori infection, around 20 weeks, mice were sacrificed at 36 weeks. Significant reductions in mean body weights were noted in control group, whereas no body weight changes in group treated with PD-MSCs (P<0.01). Significant changes in pathological scores, including inflammation, gastric atrophy, erosions/ulcers, and dysplastic changes were noted in control group (P<0.01), but significantly decreased in PD-MSCs/CM treated group. Lgr5+ expressions along with Ki-67, H+/K+-ATPase, and Musashi-1 were all significantly increased, whereas inflammatory mediators, MMP, apoptotic executors were significantly decreased in PD-MSCs group compared to control group (p<0.001). Our model that H. pylori-initiated, high salt diet-promoted gastric atrophic gastritis showed significant phyla/genus changes in fecal microbiota, but PD-MSCs/CM-treated group showed changes similar as seen in normal control. Conclusively, administration of PD-MSCs or their conditioned media can be anticipating rejuvenating agent to block the progression of H. pylori-associated premalignant lesions.